Assessment of nurses’ knowledge and practice of pressure injuries prevention for critically ill patients in Rwanda: a cross-sectional study - Sophie Mukantwari; Emmanuel Bikorimana; Liberatha Rumagihwa; Ime U. Akaninyene; Christian Ntakirutimana; Joseph Mucumbitsi; Thierry Claudien Uhawenimana; David Ikwuka (BMC Nursing)
Abstract Background Pressure injuries are costly and can lead to mortality and psychosocial consequences if not managed effectively. Proper management of pressure injuries is crucial for quality nursing care. However, there is limited research on nurses’ knowledge and practices in preventing and managing pressure injuries among critically ill patients in Rwanda. In addition, barriers affecting nurses’ practices in this area also need further investigation in order to inform the interventions to improve nursing care of patients with pressure injuries in Rwandan hospitals. Methodology A cross-sectional study involving 129 health nurses was conducted to determine their knowledge and practice levels regarding the prevention of pressure injuries in critically ill patients, and barriers impeding practice in this area. The research modified the Pieper-Zulkowski Pressure Ulcer Knowledge Test to evaluate the knowledge of nurses concerning the prevention of pressure injuries. A 33-item instrument drawn from pressure ulcer risk assessment and prevention toolkits established by the Agency for Healthcare Research and Quality was used to assess nurses’ practices. Additionally, barriers influencing nurses’ knowledge and practices related to the prevention of pressure injuries were evaluated through questions derived from a comparable study conducted in Ethiopia. Descriptive statistics were computed for each variable. Mean scores were computed to categorize nurses’ level of knowledge and practice. Logistic regression analysis was employed to examine the influence of sociodemographic factors and training on the nurses’ knowledge and practice, with a statistical significance set at a p-value less than 0.05. Results The study found that 40.0% of nurses had inadequate knowledge towards pressure injury prevention, and 60.0% reported that they inadequately practiced pressure injury prevention among critically ill patients. Nurses who have not been trained in pressure injury prevention have a 52.4% reduction in the odd of having adequate practice compared to those who have been trained (OR 0.476; 95% CI 0.211–0.996). Heavy workload, inadequate staff, shortage of equipments, presence of other priorities than pressure injury prevention, inadequate training coverage of pressure injury prevention were the most prevalent barriers reported. Conclusion The evaluation of nurses’ knowledge and practices on pressure injury prevention in critically ill patients at the study setting found that while nurses have satisfactory knowledge, their practical application is lacking due to factors like high workloads and insufficient staffing. The study recommends caution in interpreting the results due to a limited sample size, suggesting further research to guide improvements in nursing practices.